Numerical modeling of a two story third-scale reinforced masonry shear wall building subjected to quasi-static lateral loading. (15th February 2019) - Bedeir, Hassan; Shedid, Marwan; Okail, Hussein; Hamdy, Osama
Highlights: A modeling approach is proposed to capture the behavior of a RCM shear wall building subjected to Quasi-Static cyclic lateral load. Macro-models are developed for individual walls and refined to match experimental results. Values for the factors controlling the behavior of wall models under cyclic lateral loads are proposed. Non-linear torsional behavior of flanged walls has a considerable effect on the behavior of a building subjected to rotation under lateral load. An approach for modeling of structures taking into account the global behavior of the building and the interaction between its components is presented. Abstract: This paper presents numerical modeling of a two-story third-scale reinforced concrete masonry building composed of walls in orthogonal directions and subjected to quasi-static cyclic lateral loading up to failure. OpenSees and Response-2000 were used to capture the behavior at the section level as well as that at the element and system levels. The results of ten experimentally tested individual walls were used to verify the modeling approach that was used to generate the building model. The models were able to accurately capture the response of individual walls and that of the tested building. Force based elements were used to represent the walls and values for the factors controlling the cyclic behavior of masonry and steel material models used were recommended. The maximum error obtained for the strength of all wall models and for the building model was 4% and 12% respectively. Numerical results showed that overall ductility of the building was higher than that of its constituent walls especially under eccentric load which was consistent with experimental results. The torsional response of flanged walls was found to be essential for the accurate representation of the building behavior under eccentric lateral loading.